Direct and indirect selection and index selection in broiler line - Stela Adami Vayego (Semina: Ciências Agrárias, 2014)
Selection methods were compared direct and indirect selection and index selection related to productive traits, using information from 1962 female and 3870 male in maternal and paternal broiler line. Index selection can result in better genetic gains observed in the procedures for direct and indirect selection. In the paternal line, the selection by I1=1.67 (P42) + 1.02 (Cpeito) correspond to expected genetic gain per generation, compared to the average feature of 10.86% and 10.42%. In the maternal line, the selection by I1 = 0.005 (P42) – 0.018 (IMS) correspond to expected genetic gain per generation, compared to the average feature of 2.9% and – 0.1%, respectively.